2022
DOI: 10.1021/acssuschemeng.1c08193
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Pyrolysis Using a Nickel-Functionalized Chemically Activated Biochar Catalyst: Insight into Process Kinetics, Products, and Mechanism

Abstract: The present study highlighted the impact of biochar (BC)-based catalysts on catalytic pyrolysis of pine needle biomass. Thermogravimetric plots showed positive influence of catalysts by indicating reduction in the temperature requirement of the process. The same had also been stated through process kinetics by demonstrating reduction in the process’s activation energy (E a). E a had been reduced from 25.95 kJ/mol in noncatalytic pyrolysis to 20.79, 15.20, 10.52, 13.99, and 9.69 kJ/mol for BC, Ni/BC, Ni/BC-ZnCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The goal of the investigation is to determine the environmental footprints of the production of bio-oil through the biochar-based catalytic pyrolysis process and its postutilization through combustion, along with the identification of the major environmental hotspots in the process life cycle. A total of six different processes were considered: (1) noncatalytic pyrolysis, (2) biochar (BC) catalyzed pyrolysis, (3) nickel doped biochar (Ni/BC) catalyzed pyrolysis, (4) nickel doped ZnCl 2 activated biochar (Ni/BC-ZnCl 2 ) catalyzed pyrolysis, (5) nickel doped H 3 PO 4 activated biochar (Ni/BC-H 3 PO 4 ) catalyzed pyrolysis, and (6) nickel doped NaOH activated biochar (Ni/BC-NaOH) catalyzed pyrolysis . The process was modeled with GaBi software (10.5.1.124 version).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of the investigation is to determine the environmental footprints of the production of bio-oil through the biochar-based catalytic pyrolysis process and its postutilization through combustion, along with the identification of the major environmental hotspots in the process life cycle. A total of six different processes were considered: (1) noncatalytic pyrolysis, (2) biochar (BC) catalyzed pyrolysis, (3) nickel doped biochar (Ni/BC) catalyzed pyrolysis, (4) nickel doped ZnCl 2 activated biochar (Ni/BC-ZnCl 2 ) catalyzed pyrolysis, (5) nickel doped H 3 PO 4 activated biochar (Ni/BC-H 3 PO 4 ) catalyzed pyrolysis, and (6) nickel doped NaOH activated biochar (Ni/BC-NaOH) catalyzed pyrolysis . The process was modeled with GaBi software (10.5.1.124 version).…”
Section: Methodsmentioning
confidence: 99%
“…Biochar is a carbon-rich coproduct that has several potential applications as fuel, catalyst support material, soil amendment, etc. The noncondensable gases (NCGs) produced from catalytic/noncatalytic pyrolysis consist of CO 2 (46.12–52.46 mol %), CO (19.11–31.66 mol %), CH 4 (9.59–12.37 mol %), and H 2 (9.85–19.71 mol %). , The increment in CO 2 proportions in the evolved gases after catalyst addition elucidates the deoxygenation tendency of the employed biochar-based catalysts. The gases produced from the noncatalytic/catalytic process have a sufficient heating value (∼8.66–10.21 MJ/Nm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Metal loading is a widely used method for biochar activation. The presence of metallic sites improves the acidity of biochar . Sun et al revealed that biochar activated with ZnCl 2 showed a maximum selectivity of 47.6% for aromatics from plastic catalytic pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of metallic sites improves the acidity of biochar. 16 Sun et al 17 revealed that biochar activated with ZnCl 2 showed a maximum selectivity of 47.6% for aromatics from plastic catalytic pyrolysis. The reduction process that uses a reducing agent at high temperatures is a widely adopted strategy for stimulating the activity of metallic sites on the catalyst support.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the noncatalytic pyrolysis of SS, the evolution curve of CO 2 showed three peaks located at 300, 672, and 817 °C. The appearance of the peak at 300 °C was attributed to the decarboxylation and decarbonylation reactions of organic compounds in SS, 45 the peak at 672 °C was attributed to the decomposition of carbonates, 9 and the peak at 817 °C was probably due to the redox reactions of the carbon residue of SS pyrolysis with metal oxides in SS. 46 With the addition of Calcined CS, there was a certain increase in the peak located at 300 °C, which indicated that Calcined CS could promote decarboxylation and decarbonylation reactions of organic compounds.…”
Section: ■ Introductionmentioning
confidence: 99%